ANALISIS HARGA PANGAN POKOK TERHADAP KETAHANAN PANGAN DI INDONESIA - Maharestri Rahmi Widarso; Sartika Djamaluddin (Universitas Sebelas Maret, 2024)
Food security ensures that sufficient, high-quality food is accessible to everyone for optimal consumption. Rising food prices can severely impact food security, especially for economically vulnerable groups. This research investigates the relationship between staple food prices and food security in Indonesia, focusing on factors like rice energy intake, egg protein intake, Gross Regional Domestic Product (GRDP) per capita, and regional conditions on Java, Bali, and other islands. Data from all Indonesian provinces for 2018-2020 is analyzed using the Ordinary Least Squares (OLS) regression method. The Food Security Index (IKP) comes from the National Food Agency’s Food Security Index Book, and food price data is sourced from the National Strategic Food Price Information Center (PIHPS). Control data such as GRDP per capita is from the Central Statistics Agency (BPS), while rice energy and egg protein intake data are from the Ministry of Agriculture’s Food Consumption Directory. The analysis reveals that rising rice prices from 2018 to 2020 significantly negatively affected food security. The study recommends evaluating rice price policies to maintain stability and enhance food accessibility. Similar evaluations for egg prices are also suggested to ensure protein availability for the community.